Silica sol containing silica having hydrophilic groups on its surface, insulating resin composition, and insulating coated conductor.

JP2026166307APending Publication Date: 2026-10-14NISSAN CHEM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2025059168
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0010】 本発明のシリカゾルを用いることで、導体上に、シリカゾル及び窒素含有ポリマーを含む絶縁性樹脂組成物を被覆し硬化させて得た2層以上の層からなる絶縁性樹脂において、該絶縁性樹脂を構成する層同士の剥離を抑制することができる。このため、絶縁性樹脂の絶縁耐性を向上させることができる。本発明では、「絶縁性樹脂を構成する層中に特定の平均一次粒子径のシリカ粒子を含む場合、このシリカ粒子により絶縁性樹脂を構成する層の間の密着性は低下しやすくなり、指向された物性が損なわれる」という従来技術の課題を解決することができる。すなわち、本発明では、シリカ粒子がその表面に特定の親水性基を有するため、絶縁性樹脂を構成する層どうしの密着性を向上させることができる。この結果、絶縁性樹脂を構成する層どうしの剥離を抑制することができ、絶縁性樹脂中に絶縁性が劣る部位が生じない。従って、シリカ粒子を含む絶縁性樹脂は導体に対する強固な被覆層を形成することができ、放電による絶縁破壊から導体を有効に保護することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166307000001
    Figure 2026166307000001
  • Figure 2026166307000002
    Figure 2026166307000002
  • Figure 2026166307000003
    Figure 2026166307000003
Patent Text Reader

Abstract

The objective is to provide a silica sol that prevents the layers constituting the insulating resin from peeling off from each other when a conductor is coated with an insulating resin composition containing silica sol and a nitrogen-containing polymer, and the insulating resin composition is cured to obtain an insulating resin consisting of two or more layers. [Solution] A silica sol comprising a nitrogen-containing solvent and silica particles dispersed in the nitrogen-containing solvent, wherein the silica particles have an average primary particle diameter of 5 to 100 nm, and at least a portion of the silica particles have hydrophilic groups on their surface that include hydroxyl groups bonded to carbon atoms and originate from the hydrolysis of silane compound (a), and the polarity term (δP1) constituting the Hansen solubility parameter (HSP) of hydrosilane (a), in which the alkoxy group of silane compound (a) is substituted with a hydrogen atom, is 2.0 to 30.0 MPa. 0.5 The hydrogen bonding term (δH1) is 3.0-30.0 MPa. 0.5 That is silica sol.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a silica sol containing silica particles dispersed in a nitrogen-containing solvent, an insulating resin composition containing the silica sol, and an insulating coated wire. [Background technology]

[0002] A method has been disclosed in which the hydroxyl groups on the surface of inorganic oxide particles such as silica react with an alcohol to introduce alkoxysilyl groups and organicize them, thereby obtaining an inorganic oxide sol dispersed in an organic solvent such as toluene. In this method, a silica sol is disclosed obtained by reacting methanol-dispersed silica sol with phenyltrimethoxysilane and dispersing it in toluene solvent (see Patent Document 1).

[0003] Furthermore, a silica sol obtained by solvent substitution of a methanol-dispersed silica sol with acetonitrile to obtain an acetonitrile-methanol mixed solvent-dispersed silica sol, and then reacting it with phenyltrimethoxysilane has been disclosed (see Patent Document 2).

[0004] Furthermore, a silica sol in which the surface of silica particles is modified with an aluminum compound has been disclosed (see Patent Document 3).

[0005] Furthermore, an aluminum-containing silica sol dispersed in a nitrogen-containing solvent and an insulating resin composition using the same are disclosed (see Patent Document 4).

[0006] Furthermore, an enameled wire is disclosed in which a resin coating layer obtained by blending silicon oxide powder and glycidoxypropyltrimethoxysilane is provided directly above the conductor (see Patent Document 5). [Prior art documents] [Patent Documents]

[0007] [Patent Document 1] Japanese Patent Publication No. 2005-200294 [Patent Document 2] International Publication No. 2009-008509 brochure [Patent Document 3] Japanese Patent Publication No. 2011-026183 [Patent Document 4] International Publication No. 2022-097694 [Patent Document 5] Japanese Patent Publication No. 2000-331539 [Overview of the project] [Problems that the invention aims to solve]

[0008] An insulating resin consisting of two or more layers is obtained by coating a conductor with an insulating resin composition containing silica sol and a nitrogen-containing polymer, and then curing the insulating resin composition. However, the inventors have found that in this process, the layers constituting the insulating resin consisting of two or more layers are prone to peeling, which can impair the intended physical properties. The present invention provides a silica sol in which the layers constituting the insulating resin are less likely to peel off from one another. [Means for solving the problem]

[0009] In exploring means to solve the above problems, it was discovered that a silica sol with certain properties may improve the adhesion between insulating resin layers. The inventors further investigated and completed the present invention. The embodiments of the present invention are as follows. However, the present invention is not limited to the following. [1] A silica sol comprising a nitrogen-containing solvent and silica particles dispersed in the nitrogen-containing solvent, The silica particles have an average primary particle diameter of 5 to 100 nm. At least a portion of the silica particles have hydrophilic groups on their surface that originate from the hydrolysis of silane compound (a) and contain hydroxyl groups bonded to carbon atoms. The polarity term (δP1) constituting the Hansen solubility parameter (HSP) of hydrosilane (a), obtained by substituting the alkoxy group of the silane compound (a) with a hydrogen atom, is between 2.0 and 30.0 MPa. 0.5The hydrogen bonding term (δH1) is 3.0-30.0 MPa. 0.5 That is silica sol. [2] Interaction distance D between the hydrosilane (a) and the matrix resin unit structure represented by the following formula (1) x 17.0 MPa 0.5 The following applies: The interaction distance D x This is the silica sol described in [1] above, represented by the following formula (A). [ka]

number

number

[10] Interaction distance D between the silane compound (c) having all the organic groups constituting the hydrophilic group and all the organic groups constituting the hydrophobic group and the matrix resin unit structure represented by the following formula (1) z1 17.0 MPa 0.5 The following applies: The interaction distance D z1 This is the silica sol described in [8] above, represented by the following formula (D). [ka]

number

[11] Interaction distance D between the silane compound (c) having all the organic groups constituting the hydrophilic group and all the organic groups constituting the hydrophobic group and the matrix resin unit structure represented by the following formula (2) z2 17.0 MPa 0.5 The following applies: The interaction distance D z2 This is the silica sol described in [8] above, represented by the following formula (E). [ka]

number

[12] The silica sol according to [1] above, wherein the nitrogen-containing solvent is an amide solvent.

[13] The silica sol according to

[12] above, wherein the nitrogen-containing solvent is dimethylacetamide, dimethylformamide, N-methylpyrrolidone, or N-ethylpyrrolidone.

[14] An insulating resin composition comprising a silica sol as described in any one of the above items [1] to

[13] and a nitrogen-containing polymer.

[15] The insulating resin composition according to

[14] , wherein the content of the nitrogen-containing polymer is 1 to 100 parts by mass per 1 part by mass of silica particles contained in the silica sol.

[16] The insulating resin composition according to

[14] , wherein the nitrogen-containing polymer is polyimide, polyamide, polyamic acid, polyamideimide, polyetherimide, or polyesterimide.

[17] The insulating resin composition according to

[16] , wherein the nitrogen-containing polymer is a polymer containing repeating units represented by the following formula (8). [ka]

[18] Conductors and, A cured layer of the insulating resin composition described in

[14] above, which covers the aforementioned conductor, comprising a cured layer consisting of two or more layers, An insulating coated conductor having [a certain characteristic]. [Effects of the Invention]

[0010] By using the silica sol of the present invention, it is possible to suppress delamination between layers constituting the insulating resin in an insulating resin consisting of two or more layers obtained by coating and curing an insulating resin composition containing silica sol and nitrogen-containing polymer on a conductor. Therefore, the dielectric strength of the insulating resin can be improved. The present invention solves the problem of the prior art in that "when silica particles of a specific average primary particle diameter are included in the layers constituting the insulating resin, these silica particles tend to reduce the adhesion between the layers constituting the insulating resin, impairing the intended physical properties." In other words, in the present invention, since the silica particles have specific hydrophilic groups on their surface, the adhesion between the layers constituting the insulating resin can be improved. As a result, delamination between the layers constituting the insulating resin can be suppressed, and no areas with inferior insulating properties are created in the insulating resin. Therefore, an insulating resin containing silica particles can form a strong coating layer on the conductor, effectively protecting the conductor from dielectric breakdown due to discharge. [Modes for carrying out the invention]

[0011] The technical scope of the present invention may include embodiments having numerical values ​​greater than or less than the numerical values ​​defining the present invention, insofar as they achieve the intended effects of the present invention. (Silica sol) The present invention relates to a silica sol comprising a nitrogen-containing solvent and silica particles dispersed in the nitrogen-containing solvent, Silica particles have an average primary particle diameter of 5-100 nm. At least a portion of the silica particles have hydrophilic groups on their surface that originate from the hydrolysis of silane compound (a) and have hydroxyl groups bonded to carbon atoms. The polarity term (δP1) constituting the Hansen solubility parameter (HSP) of hydrosilane (a), obtained by substituting the alkoxy group of silane compound (a) with a hydrogen atom, is between 2.0 and 30.0 MPa. 0.5 The hydrogen bonding term (δH1) is 3.0-30.0 MPa. 0.5 This concerns silica sol. Furthermore, when we say that silica particles "have" hydrophilic and hydrophobic groups, it means that the surface of the silica particle and the hydrophilic group, and the surface of the silica particle and the hydrophobic group, respectively, form covalent bonds. In other words, when we say that silica particles "have" hydrophilic and hydrophobic groups, it means that at least one -O-Si- in each of the hydrophilic and hydrophobic groups and the Si present on the surface of the silica particle form a covalent siloxane bond (-Si-O-Si-). Furthermore, the hydrophilic group has a hydroxyl group bonded to a carbon atom that constitutes the organic group bonded to Si, which will be described later. The hydrophobic group does not have a hydroxyl group bonded to the carbon atom that constitutes the organic group bonded to Si, which will be described later.

[0012] In this invention, silica particles having a specific average primary particle size have a hydrophilic group on their surface, which is derived from the hydrolysis of silane compound (a) and has a hydroxyl group bonded to a carbon atom. This hydrophilic group has a polarity term (δP1) of the Hansen solubility parameter (HSP) in hydrosilane (a), obtained by substituting the alkoxy group of silane compound (a) with a hydrogen atom, of 2.0 to 30.0 MPa. 0.5 The hydrogen bonding term (δH1) is 3.0-30.0 MPa. 0.5 These polymers have excellent affinity for nitrogen-containing polymers. Specifically, these nitrogen-containing polymers are synthesized, for example, from diamines and acid anhydrides, and possess hydrophilic parts such as imide skeletons, carboxyl groups, and amide bonds. Furthermore, the unit structures corresponding to the repeating units having both substructures of the nitrogen-containing polymer (for example, the matrix resin unit structures represented by formulas (1) and (2) above) have a polarity term in the Hansen solubility parameter (HSP) of 2.0 to 30.0 MPa. 0.5 The hydrogen bonding term is 3.0 to 30.0 MPa. 0.5 This is the extent of the relationship. Thus, since the polarity term (δP1) and hydrogen bonding term (δH1) of hydrosilane (a) corresponding to the hydrophilic groups present on the surface of the silica particles are similar to the polarity term and hydrogen bonding term of the unit structure corresponding to the repeating units constituting the nitrogen-containing polymer, it is considered that silica particles have excellent affinity for nitrogen-containing polymers.

[0013] The polar term (δP1) of hydrosilane (a), obtained by substituting a hydrogen atom for the alkoxy group of silane compound (a), is 2.0 to 30.0 MPa. 0.5 The pressure range is 2.0 to 20.0 MPa. 0.5 Preferably, 3.0 to 10.0 MPa 0.5 This is preferable. The hydrogen bonding term (δH1) of hydrosilane (a), obtained by substituting the alkoxy group of silane compound (a) with a hydrogen atom, is 3.0 to 30.0 MPa. 0.5 The pressure range is 5.0 to 20.0 MPa. 0.5 Preferably, 8.0 to 15.0 MPa 0.5 This is preferable. By having the polarity term (δP1) and hydrogen bonding term (δH1) of hydrosilane (a) within the above range, the silica particles have a superior affinity for nitrogen-containing polymers, and the adhesion between the layers constituting the insulating resin can be further improved.

[0014] The following provides a detailed explanation of HSP. The Hansen solubility parameter (HSP; hereafter referred to as "HSP") is a physical property defined as the square root of the cohesive energy density, and is calculated according to the following formula (A).

number

[0015] Below, we will give examples of hydrophilic groups and explain the hydrosilane (a) corresponding to each hydrophilic group. As shown in formulas (I) to (III) below, the portion represented by -O- in the hydrophilic group corresponds to the alkoxy group of silane compound (a). Therefore, the portion represented by -O- in the hydrophilic group is converted to an alkoxy group. Furthermore, since the alkoxy group portion of silane compound (a) does not affect its affinity for nitrogen-containing polymers, it is converted to a hydrogen atom to obtain hydrosilane (a). For the hydrosilane (a) thus converted, the polarity term (δP1) and hydrogen bonding term (δH1) are calculated. The polarity term (δP1) and hydrogen bonding term (δH1) can be calculated using the calculation software Winmòstar (manufactured by CrossAbility Co., Ltd.). [ka] (R 1 '~R 3 ' is R in equations (3a) to (3c) described later. 1 '~R 3 (It has the same meaning as ', and R' represents an organic group.)

[0016] Interaction distance D between hydrosilane (a) and the matrix resin unit structure represented by the following formula (1) x 17.0 MPa0.5 Preferably, the following is true: 16.0 MPa 0.5 It is more preferable that the following conditions be met: 15.5 MPa 0.5 The following is even more preferable. [ka] Here, the interaction distance D x This is also called the HSP distance and is expressed by the following formula (A).

number

[0017] Interaction distance D between hydrosilane (a) and the matrix resin unit structure represented by the following formula (2) y 17.0 MPa 0.5 Preferably, the following is true: 16.0 MPa 0.5 The following is more preferable: 15.0 MPa 0.5 The following is even more preferable: [ka] Here, the interaction distance D y This is also called the HSP distance and is expressed by the following formula (B).

number

[0018] interaction distance D x and D y As long as the above range is maintained, the silica particles have a better affinity for nitrogen-containing polymers having repeating unit structures corresponding to the matrix resin unit structures represented by formulas (1) and (2) above, and the adhesion between the layers constituting the insulating resin can be further improved.

[0019] An insulating resin composition prepared under the following preparation conditions is applied to a glass plate and heated at 290°C for 1 hour in an atmospheric environment to form a first silica-containing polyimide film having a thickness of 15 to 20 μm. An insulating resin composition prepared under the following preparation conditions is applied to a first silica-containing polyimide film, and heated at 290°C for 1 hour in an atmospheric environment to form a second silica-containing polyimide film having a thickness of 15 to 20 μm. Ten of the two-layer films, each consisting of a first and a second silica-containing polyimide film, are prepared by peeling them off the glass plate, and each of the two-layer films is subjected to a tensile test. The percentage of delamination between the first silica-containing polyimide film and the second silica-containing polyimide film, calculated as (number of times the two-layer film delaminates) / (10 times) × 100, is preferably less than 30%, more preferably less than 20%, and even more preferably less than 10%. [Preparation conditions for insulating resin compositions] An insulating resin composition is prepared by using a polyamic acid (DDE and PMDA polymerized in an equimolar 1:1 ratio, with a solid content of 17% by mass and a weight-average molecular weight of 63,000) consisting of 4,4'-diaminodiphenyl ether (DDE) and pyromellitic anhydride (PMDA) as the resin, and adding the silica sol in a mass ratio of resin / SiO2 = 80 / 20.

[0020] At least a portion of the silica particles have hydrophobic groups on their surface that are derived from the hydrolysis of silane compound (b) and do not contain hydroxyl groups bonded to carbon atoms, and the interaction distance D between hydrosilane (a) and hydrosilane (b) obtained by substituting the alkoxy group of silane compound (b) with a hydrogen atom. z 5.0 MPa 0.5 Preferably, the pressure should be 7.0 MPa. 0.5 It is more preferable that the value be greater than or equal to 9.0 MPa. 0.5 It is even more preferable if the result is as described above. Here, the interaction distance D z This is expressed by the following formula (C).

number

[0021] In this invention, to evaluate the state of hydrophobic groups on the surface of silica particles using HSP, a substructure of the hydrophobic group that can interact with a nitrogen-containing polymer is converted into a single substance, and the dispersion term, polar term, and hydrogen bonding term constituting the HSP of this single substance are calculated. More specifically, in the silane compound (b) from which the hydrophobic group originates, the dispersion term, polar term, and hydrogen bonding term constituting the HSP of hydrosilane (b), in which the alkoxy group involved in hydrolysis and siloxane bonding with the silica particle surface is replaced with a hydrogen atom, are calculated. It has been confirmed in advance that the portion of the hydrophobic group corresponding to the alkoxy group of the silane compound (b) is located near the silica particle surface and therefore does not affect the affinity to the nitrogen-containing polymer.

[0022] Below, we will give examples of hydrophobic groups and explain the hydrosilane (b) corresponding to each hydrophobic group. As shown in equations (IV) to (VI) below, the portion represented by -O- in the hydrophobic group corresponds to the alkoxy group of silane compound (b). Therefore, the portion represented by -O- in the hydrophobic group is converted to an alkoxy group. Furthermore, since the alkoxy group portion of silane compound (b) does not affect its affinity for nitrogen-containing polymers, it is converted to a hydrogen atom to obtain hydrosilane (b). For the hydrosilane (b) thus converted, HSP, δD4, δP4, and δH4 are calculated according to equation (A) above. Note that HSP, etc., can be calculated using the calculation software Winmòstar (manufactured by CrossAbility Co., Ltd.). [ka] (R 4 '~R 6 ' is R in equations (4a) to (4c) described later. 4 '~R 6 (It has the same meaning as ', and R' represents an organic group.)

[0023] The interaction distance D between the silane compound (c) having all the organic groups constituting the hydrophilic group and all the organic groups constituting the hydrophobic group and the matrix resin unit structure represented by the following formula (1) z1 17.0 MPa 0.5 Preferably, the following is true: 16.0 MPa 0.5 It is more preferable that the following conditions be met: 15.5 MPa 0.5 The following is even more preferable. [ka] Here, the interaction distance D z1 This is expressed by the following formula (D).

number

[0024] The interaction distance D between the silane compound (c) having all the organic groups constituting the hydrophilic group and all the organic groups constituting the hydrophobic group and the matrix resin unit structure represented by the following formula (2) z2 17.0 MPa 0.5 The following is preferable. [ka] Here, the interaction distance D z2 This is expressed by the following formula (E).

number

[0025] In this embodiment, when silica particles have hydrophilic and hydrophobic groups on their surface, the interaction between the surface of the silica particles and the nitrogen-containing polymer is defined, taking into account both the hydrophilic and hydrophobic groups.

[0026] The silane compound (c) is determined according to the following rules (i) to (iii). (1) When the total number of organic groups on the hydrophilic group and the hydrophobic group is 3 or less, a hydrosilane in which one Si atom is bonded to an organic group on the hydrophilic group and a hydrophobic group, and hydrogen atoms are bonded to the remaining Si atoms, is defined as silane compound (c). (ii) When the total number of organic groups possessed by the hydrophilic group and the hydrophobic group is 4 or 5, a hydrosilane formed by a disilane group -Si-Si- consisting of two Si atoms, in which the organic group possessed by the hydrophilic group is bonded to the first Si, the organic group possessed by the hydrophobic group is bonded to the second Si, and hydrogen atoms are bonded to the remaining Si atoms, is defined as silane compound (c). (iii) When the total number of organic groups possessed by the hydrophilic group and the hydrophobic group is 6, a disilane compound in which three organic groups of the hydrophilic group are bonded to the first Si and three organic groups of the hydrophobic group are bonded to the second Si of a disilane group -Si-Si- consisting of two Si atoms is defined as silane compound (c).

[0027] The following provides specific examples of formulas (VII) to (XV) to explain how to define silane compound (c).

[0028] Formulas (VII) to (IX) below are specific examples showing the case where the hydrophilic group has three organic groups. In formula (VII) below, the total number of organic groups in the hydrophilic and hydrophobic groups is 4, so silane compound (c) is determined according to rule (ii) above. [ka] (In the above equation (VII), R 1 '~R 3 ' is R in equation (3a) described later. 1 '~R 3 ' has the same meaning as R 6 ' is R in equation (4c) described later. 6 (Has the same meaning as ')

[0029] In the following formula (VIII), the total number of organic groups in the hydrophilic and hydrophobic groups is 5, so the silane compound (c) is determined according to rule (ii) above. [ka] (In the above equation (VIII), R 1 '~R3 ' has the same meaning as R 1 ' to R 3 defined later for formula (3a); R 5 ' to R 6 ' has the same meaning as R 5 ' to R 6 ' defined later for formula (4b))

[0030] In the following formula (IX), the total number of organic groups contained in the hydrophilic group and the hydrophobic group is 6, so the silane compound (c) is determined according to the above rule (3).

Chemical Formula

[0031] The following formulas (X) to (XII) are specific examples showing the case where the hydrophilic group has 2 organic groups. In the following formula (X), the total number of organic groups contained in the hydrophilic group and the hydrophobic group is 3, so the silane compound (c) is determined according to the above rule (1).

Chemical Formula

[0032] In the following formula (XI), the total number of organic groups contained in the hydrophilic group and the hydrophobic group is 4, so the silane compound (c) is determined according to the above rule (2). [ka] (In the above equation (XI), R 2 '~R 3 ' is R in equation (3b) described later. 2 '~R 3 ' has the same meaning as R 5 '~R 6 ' is R in equation (4b) described later. 5 '~R 6 (Has the same meaning as ')

[0033] In the following formula (XII), the total number of organic groups in the hydrophilic and hydrophobic groups is 5, so the silane compound (c) is determined according to rule (ii) above. [ka] (In the above equation (XII), R 2 '~R 3 ' is R in equation (3b) described later. 2 '~R 3 ' has the same meaning as R 4 '~R 6 ' is R in equation (4a) described later. 4 '~R 6 (Has the same meaning as ')

[0034] The following formulas (XIII) to (XV) are specific examples showing the case where the hydrophilic group has one organic group. In the following formula (XIII), the total number of organic groups in the hydrophilic and hydrophobic groups is 2, so the silane compound (c) is determined according to rule (i) above. [ka] (In the above equation (XIII), R 3 ' is R in equation (3c) described later. 3 ' has the same meaning as R 6 ' is R in equation (4c) described later. 6 (Has the same meaning as ')

[0035] In the following formula (XIV), the total number of organic groups in the hydrophilic and hydrophobic groups is 3, so silane compound (c) is determined according to rule (i) above. [ka] (In the above equation (XIV), R 3 ' is R in equation (3c) described later. 3 ' has the same meaning as R 5 '~R 6 ' is R in equation (4b) described later. 5 '~R 6 (Has the same meaning as ')

[0036] In the following formula (XV), the total number of organic groups in the hydrophilic and hydrophobic groups is 4, so the silane compound (c) is determined according to rule (ii) above. [ka] (In the above equation (XV), R 3 ' is R in equation (3c) described later. 3 ' has the same meaning as R 4 '~R 6 ' is R in equation (4a) described later. 4 '~R 6 (Has the same meaning as ')

[0037] For the silane compound (c) converted as described above, the HSP is calculated. The HSP can be calculated using the calculation software WinmÑstar (manufactured by CrossAbility Co., Ltd.).

[0038] The following describes each component contained in the silica sol of the present invention, but the components of the present invention are not limited to those described below.

[0039] (1) Silica particles At least a portion of the silica particles of the present invention have a hydrophilic group on the surface of the silica particles, which is a group having a polar portion and is derived from the hydrolysis of silane compound (a) and contains a hydroxyl group bonded to a carbon atom. Silane compound (a) is a compound that, after hydrolysis, forms at least one siloxane bond represented as -Si-O-Si- with Si on the surface of the silica particles, and contains one or more hydroxyl groups after the formation of the siloxane bond. The silane compound (a) is not particularly limited as long as it has the properties described above, but examples include 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 8-glycidoxyoctyltrimethoxysilane, 3-[(3-ethyloxetan-3-yl)methoxy]propyl(trimethoxy)silane, 3-[(3-ethyloxetan-3-yl)methoxy]propyl(triethoxy)silane, 3-[(3-methyloxetan-3-yl)methoxy]propyl(trimethoxy)silane, 3-[(3-methyloxetan-3-yl)methoxy]propyl(trimethoxy)silane, 8-glycidoxyoctyltriethoxysilane, and 3-trimethoxypropyl succinic anhydride.

[0040] Examples of hydrophilic groups include those represented by the following formula (3). [ka] (In the above equation (3), R 1 , R 2 and R 3 Each of these independently represents -O- or an organic group, and R 1 , R 2 and R 3 (At least one of these groups is an organic group containing a hydroxyl group.)

[0041] In equation (3), at least one -O- forms a siloxane bond represented by -Si-O-Si- with the Si on the surface of the silica particle. Also, R 1 , R 2 and R 3 If one or two of the groups are -O-, these -O- may constitute an -OH group, form a siloxane bond represented as -Si-O-Si- with Si on the silica particle surface, or form a siloxane bond with Si atoms in other hydrophilic and hydrophobic groups present on the silica particle surface. In formula (3), the organic group is -(CH2) y Ure 12 (y is an integer from 1 to 10, R 12 Examples include alkyl groups, aryl groups, or alicyclic groups having 1 to 10 carbon atoms, in which two or more hydrogen atoms are substituted with hydroxyl groups, and vicinal diol groups.

[0042] Furthermore, the following formulas (3a) to (3c) are examples of bases represented by the above formula (3). [ka] (In the above equation (3a), R 1 ', R 2 'and R 3 ' represents an organic group, R 1 ', R 2 'and R 3 At least one of the groups is an organic group having a hydroxyl group. In formula (3a), one -O- forms a siloxane bond with the surface of the silica particle. [ka] (In the above equation (3b), R 2 'and R 3 ' represents an organic group, R 2 'and R 3At least one of the groups is an organic group having a hydroxyl group. Of the two -O- groups bonded to the Si atom in formula (3b), the first -O- forms a siloxane bond with the surface of the silica particle, while the second -O- may bond to a hydrogen atom to form a hydroxyl group, or to the surface of the silica particle, or to Si atoms in other hydrophilic and hydrophobic groups present on the surface of the silica particle. [ka] (In the above equation (3c), R 3 ' represents an organic group having a hydroxyl group. Of the three -O- groups bonded to the Si atom in formula (3c), the first -O- forms a siloxane bond with the surface of the silica particle, while the second and third -O- groups may bond to a hydrogen atom to form a hydroxyl group, or to the surface of the silica particle to form a siloxane bond, or to Si atoms in other hydrophilic and hydrophobic groups present on the surface of the silica particle to form a siloxane bond.

[0043] The groups represented by formulas (3a) to (3c) above originate from silane compound (a) (for example, a silane coupling agent). For example, at least one -O- bonded to the Si atom in formulas (3a) to (3c) above reacts with a hydroxyl group such as a silanol group present on the surface of the silica particle (A) to form a siloxane bond (covalent bond). That is, the siloxane bond (covalent bond) in (A) above is formed by the reaction of a hydroxyl group obtained by hydrolyzing the alkoxy group of silane compound (a) corresponding to the groups represented by formulas (3a) to (3c) above with a hydroxyl group such as a silanol group present on the surface of the silica particle. Examples of silane compound (a) corresponding to the groups represented by formulas (3a) to (3c) above include silane compounds in which the -O- bonded to the Si atom in formulas (3a) to (3c) above is an alkoxy group and has a group corresponding to a hydroxyl group.

[0044] The organic group having a hydroxyl group in formula (3) above is preferably -CH(OH)-CH2(OH). For example, -CH(OH)-CH2(OH) can be obtained by opening the ring of an epoxy group or oxetane group in an epoxy or oxetane silane compound (a).

[0045] The following are specific examples of groups represented by the above formula (3). [ka]

[0046] At least a portion of the silica particles may have a hydrophobic group on their surface, which is derived from the hydrolysis of silane compound (b) and does not contain a hydroxyl group bonded to a carbon atom. Silane compound (b) is a compound that, after hydrolysis, forms at least one siloxane bond represented as -Si-O-Si- with the Si on the surface of the silica particles, and after the formation of the siloxane bond, does not contain a hydroxyl group in the organic group bonded to the Si atom. The silane compound (b) is not particularly limited as long as it has the properties described above, but examples include vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-ureidopropyltrimethoxysilane, 3-isocyanatetopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, and 3-mercaptopropyltrimethoxysilane.

[0047] Examples of hydrophobic groups include the group represented by the following formula (4). [ka] (In the above equation (4), R4 , R 5 and R 6 Each of these independently represents an organic group that does not have an -O- or hydroxyl group, and R 4 , R 5 and R 6 (At least one of these groups is the aforementioned organic group.)

[0048] Furthermore, the following formulas (4a) to (4c) are examples of bases represented by the above formula (4). [ka] (In the above formula (4a), R 4 ', R 5 'and R 6 ' represents an organic group that does not have a hydroxyl group. In formula (4a), one -O- forms a siloxane bond with the surface of the silica particle. [ka] (In the above equation (4b), R 5 'and R 6 ' represents an organic group that does not have a hydroxyl group. Of the two -O- groups bonded to the Si atom in formula (4b), the first -O- forms a siloxane bond with the surface of the silica particle, while the second -O- may bond to a hydrogen atom to form a hydroxyl group, or to the surface of the silica particle, or to Si atoms in other hydrophilic and hydrophobic groups present on the surface of the silica particle. [ka] (In the above equation (4c), R 6' represents an organic group that does not have a hydroxyl group. Of the three -O- groups bonded to the Si atom in formula (4c), the first -O- forms a siloxane bond with the surface of the silica particle, while the second and third -O- groups may bond to a hydrogen atom to form a hydroxyl group, or to the surface of the silica particle to form a siloxane bond, or to Si atoms in other hydrophilic and hydrophobic groups present on the surface of the silica particle to form a siloxane bond.

[0049] Examples of the organic group in formula (4) above include alkyl groups, halogenated alkyl groups, alkenyl groups, aryl groups, or groups having a (meth)acryloyl group, a mercapto group, a ureido group, or a cyano group.

[0050] The alkyl group in formula (4) above is, for example, an alkyl group having 1 to 18 carbon atoms, specifically a methyl group, ethyl group, n-propyl group, i-propyl group, cyclopropyl group, n-butyl group, i-butyl group, s-butyl group, t-butyl group, cyclobutyl group, 1-methyl-cyclopropyl group, 2-methyl-cyclopropyl group, n-pentyl group, 1-methyl-n-butyl group, 2-methyl-n-butyl group, 3-methyl-n-butyl group, 1,1-dimethyl-n-propyl group, 1,2-dimethyl-n-propyl group, 2,2-dimethyl-n-propyl group Group, 1-ethyl-n-propyl group, cyclopentyl group, 1-methyl-cyclobutyl group, 2-methyl-cyclobutyl group, 3-methyl-cyclobutyl group, 1,2-dimethyl-cyclopropyl group, 2,3-dimethyl-cyclopropyl group, 1-ethyl-cyclopropyl group, 2-ethyl-cyclopropyl group, n-hexyl group, 1-methyl-n-pentyl group, 2-methyl-n-pentyl group, 3-methyl-n-pentyl group, 4-methyl-n-pentyl group, 1,1-dimethyl-n-butyl group, 1,2-dimethyl-n-butyl group, 1,3-dimethyl- n-butyl group, 2,2-dimethyl-n-butyl group, 2,3-dimethyl-n-butyl group, 3,3-dimethyl-n-butyl group, 1-ethyl-n-butyl group, 2-ethyl-n-butyl group, 1,1,2-trimethyl-n-propyl group, 1,2,2-trimethyl-n-propyl group, 1-ethyl-1-methyl-n-propyl group, 1-ethyl-2-methyl-n-propyl group, cyclohexyl group, 1-methyl-cyclopentyl group, 2-methyl-cyclopentyl group, 3-methyl-cyclopentyl group, 1-ethyl-cyclobutyl group, 2-ethyl-cyclo Butyl group, 3-ethyl-cyclobutyl group, 1,2-dimethyl-cyclobutyl group, 1,3-dimethyl-cyclobutyl group, 2,2-dimethyl-cyclobutyl group, 2,3-dimethyl-cyclobutyl group, 2,4-dimethyl-cyclobutyl group, 3,3-dimethyl-cyclobutyl group, 1-n-propyl-cyclopropyl group, 2-n-propyl-cyclopropyl group, 1-i-propyl-cyclopropyl group, 2-i-propyl-cyclopropyl group, 1,2,2-trimethyl-cyclopropyl group, 1,2,3-trimethyl-cyclopropyl group, 2,2,Examples include, but are not limited to, 3-trimethylcyclopropyl group, 1-ethyl-2-methylcyclopropyl group, 2-ethyl-1-methylcyclopropyl group, 2-ethyl-2-methylcyclopropyl group and 2-ethyl-3-methylcyclopropyl group, hexyl group, heptyl group, octyl group, nonyl group, decyl group, undecyl group, dodecyl group, tridecyl group, tetradecyl group, pentadecyl group, hexadecyl group, heptadecyl group, octadecyl group, etc.

[0051] Examples of halogenated alkyl groups in formula (4) above include groups in which some or all of the hydrogen atoms of the alkyl group are substituted with halogen atoms (F, Cl, Br, I, etc.).

[0052] The alkenyl group in formula (4) above is, for example, an alkenyl group having 2 to 10 carbon atoms, specifically ethenyl group, 1-propenyl group, 2-propenyl group, 1-methyl-1-ethenyl group, 1-butenyl group, 2-butenyl group, 3-butenyl group, 2-methyl-1-propenyl group, 2-methyl-2-propenyl group, 1-ethylethenyl group, 1-methyl-1-propenyl group, 1-methyl-2-propenyl group, 1-pentenyl group, 2-pentenyl group, 3-pentenyl group, 4-pentenyl group, 1-n-propylethenyl group, 1-methyl-1-butenyl group, 1-methyl-2-butenyl group, 1-methyl-3-butenyl group, 2-ethyl-2-propenyl group, 2-methyl-1-butenyl group, 2-methyl-2-butenyl group, 2-methyl-3-butenyl group Examples of but not limited to these include the tenyl group, 3-methyl-1-butenyl group, 3-methyl-2-butenyl group, 3-methyl-3-butenyl group, 1,1-dimethyl-2-propenyl group, 1-i-propylethenyl group, 1,2-dimethyl-1-propenyl group, 1,2-dimethyl-2-propenyl group, 1-cyclopentenyl group, 2-cyclopentenyl group, 3-cyclopentenyl group, 1-hexenyl group, 2-hexenyl group, 3-hexenyl group, 4-hexenyl group, 5-hexenyl group, 1-methyl-1-pentenyl group, 1-methyl-2-pentenyl group, 1-methyl-3-pentenyl group, 1-methyl-4-pentenyl group, 1-n-butylethenyl group, 2-methyl-1-pentenyl group, and 2-methyl-2-pentenyl group.

[0053] The aryl group in formula (4) above is, for example, an aryl group having 6 to 30 carbon atoms, specifically a phenyl group, naphthyl group, anthracene group, pyrene group, etc.

[0054] The (meth)acryloyl group in formula (4) above represents both an acryloyl group and a methacryloyl group. Examples of organic groups having the (meth)acryloyl group in formula (4) above include 3-methacryloxypropyl group and 3-acryloxypropyl group.

[0055] An example of an organic group having a mercapto group in formula (4) above is the 3-mercaptopropyl group.

[0056] An example of an organic group having a ureido group in formula (4) above is the 3-ureidopropyl group.

[0057] An example of an organic group having a cyano group in formula (4) above is the 3-cyanopropyl group.

[0058] The groups represented by formulas (4a) to (4c) above originate from silane compound (b) (for example, a silane coupling agent). For example, at least one -O- bonded to the Si atom in formulas (4a) to (4c) above reacts with a hydroxyl group such as a silanol group present on the surface of the silica particles (B) to form a siloxane bond (covalent bond). That is, the siloxane bond (covalent bond) of (B) above is formed by the reaction of a hydroxyl group obtained by hydrolysis of the alkoxy group of the silane compound (b) corresponding to the groups represented by formulas (4a) to (4c) above with a hydroxyl group such as a silanol group present on the surface of the silica particles. Examples of silane compound (b) corresponding to the groups represented by formulas (4a) to (4c) above include silane compound (b) in which the -O- bonded to the Si atom in formulas (4a) to (4c) above is an alkoxy group.

[0059] The following are specific examples of groups represented by the above formula (4). [ka] [ka] [ka]

[0060] The silica particles contained in the silica sol of the present invention have an average primary particle diameter of 5 to 100 nm. When the average primary particle diameter of silica particles is 5 to 100 nm, the adhesion between layers constituting the insulating resin tends to decrease, but the present invention has a unique structure that can improve the adhesion between layers constituting the insulating resin. The average primary particle diameter of the silica particles is preferably 10 to 70 nm, more preferably 10 to 50 nm, and even more preferably 10 to 30 nm. The particle diameter (nm) measured by the nitrogen gas adsorption method (BET method) can be used as the average primary particle diameter of the silica particles. The particle diameter (average primary particle diameter D (nm)) measured by the nitrogen gas adsorption method (BET method) is equal to the specific surface area S (m²) measured by the nitrogen gas adsorption method. 2 ( / g) and density ρ (g / cm³) 3 ) is given by the formula D(nm) = 6000 / ρ × S. In this invention, the density ρ of silica particles is 2.2 (g / cm³). 3 ) was used.

[0061] Furthermore, the silica particles contained in the silica sol of the present invention exhibit good dispersibility in nitrogen-containing solvents, and the average secondary particle diameter measured by dynamic light scattering (DLS) in a nitrogen-containing solvent is preferably in the range of 3 to 500 nm, more preferably 3 to 100 nm, and even more preferably 10 to 70 nm.

[0062] (2) Nitrogen-containing solvent The nitrogen-containing solvent used in the present invention has a functional group containing at least a nitrogen atom (nitrogen-containing functional group). Examples of nitrogen-containing functional groups include amino groups, nitro groups, and cyano groups. The nitrogen-containing solvent used in the present invention is preferably an amide-based solvent in which a nitrogen-containing functional group and a carbonyl group exist within one molecule of the solvent, and examples include chain-like structures and cyclic structures. Examples of nitrogen-containing functional groups include amino groups, nitro groups, and cyano groups, but the use of an amino group is preferred. The amino group and carbonyl group can be adjacent to each other or separated by a carbon atom, but they can be used as, for example, an amide bond, and amide-based solvents are preferably used.

[0063] Specific examples of nitrogen-containing solvents include, for example, dimethylformamide, diethylformamide, dimethylacetamide, diethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone, tetramethylurea, hexamethylphosphoric triamide, dimethylacrylamide, acryloylmorpholine, hydroxyethylacrylamide, isopropylacrylamide, diethylacrylamide, dimethylaminopropylacrylamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, dimethylaminopropylacrylamide methyl chloride quaternary salt, dimethylaminoethyl acrylate benzyl chloride quaternary salt, and the like.

[0064] Preferably, examples of nitrogen-containing solvents include dimethylacetamide, dimethylformamide, N-methylpyrrolidone, and N-ethylpyrrolidone.

[0065] In this invention, other solvents may be included in the nitrogen-containing solvent, as long as the effect is not impaired.

[0066] That is, the total solvent may contain nitrogen-containing solvents in proportions of 50-100% by volume, 90-100% by volume, 98-100% by volume, or 99-100% by volume, and other solvents may be contained in proportions of 0% to less than 50% by volume, 0% to less than 10% by volume, 0% to less than 2% by volume, or 0% to less than 1% by volume.

[0067] Other solvents include water, ketone solvents, ester solvents, alcohol solvents, glycol ether solvents, hydrocarbon solvents, halogen solvents, ether solvents, glycol solvents, and amine solvents.

[0068] Examples include ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, and cyclohexanone; ester solvents such as methyl acetate, ethyl acetate, and butyl acetate; alcohol solvents such as methanol, ethanol, isopropanol, and benzyl alcohol; glycol ether solvents such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monopropyl ether, and diethylene glycol monobutyl ether; hydrocarbon solvents such as benzene, toluene, xylene, n-hexane, and cyclohexane; halogen solvents such as dichloromethane, trichloroethylene, and perchloroethylene; ether solvents such as dioxane, diethyl ether, and tetrahydrofuran; glycol solvents such as ethylene glycol, diethylene glycol, propylene glycol, and polyethylene glycol; and amine solvents such as monoethanolamine, diethanolamine, triethanolamine, monoisopropanolamine, diisopropanolamine, triisopropanolamine, N-methylethanolamine, and 2-amino-2-methyl-1-propanol.

[0069] (Insulating resin composition) The insulating resin composition of the present invention comprises the above-mentioned silica sol and a nitrogen-containing polymer. The content of the nitrogen-containing polymer in the insulating resin composition is preferably 1 to 100 parts by mass, more preferably 1 to 50 parts by mass, and even more preferably 1 to 30 parts by mass, per 1 part by mass of silica particles contained in the silica sol. Examples of nitrogen-containing polymers include polyimide, polyamide, polyamic acid, polyamideimide, polyetherimide, or polyesterimide.

[0070] Examples of nitrogen-containing polymers include polymers containing repeating units represented by the following formula (8). More specifically, polyamic acid can be cited as a polymer containing repeating units represented by the following formula (8). [ka]

[0071] By repeating the process of coating a conductor requiring insulation with an insulating resin composition and heating and curing the insulating resin composition at a temperature at which the nitrogen-containing solvent evaporates, two or more times, an insulating resin coating layer consisting of two or more layers can be formed on the surface of the conductor. The heating temperature for removing the nitrogen-containing solvent is determined by temperature and pressure, but at atmospheric pressure it is approximately 150°C to 300°C, or approximately 150°C to 400°C for imidization of the nitrogen-containing polymer.

[0072] (Insulated coated wire) The conductors mentioned above are, for example, metal wires, and copper wires are particularly commonly used. Copper wires are coated with an enamel coating layer and used as electric wires in industrial and household motors, transformers, coils, etc. Insulated coated conductors can be manufactured by coating enamel-coated copper wire with the insulating resin composition of the present invention, or by directly coating the copper wire with the insulating resin composition instead of enamel. This insulated coated conductor has a conductor and multiple coating layers of insulating resin (cured products of the insulating resin composition) that cover the conductor, and is typically used as an insulated coated conductor for electric vehicles. High voltages of 400V or more may be loaded inside electric vehicles, but by using the insulated coated conductor of the present invention, excellent resistance to such high voltages can be achieved.

[0073] The insulating coated conductor of the present invention has, for example, the following excellent insulating properties and flexibility. Flexibility is measured in accordance with JIS C 3216-3 Section 5. The insulating coated conductor of the present invention is an insulating coated conductor having two or more coating layers of insulating resin adjusted to a silica concentration of 20% by mass and a thickness of 35 μm, wherein it is preferable that the coating layer of the insulating resin has a flexibility of 1d to 2d. However, the flexibility is determined by finding the minimum winding diameter d at which a 20% stretched insulating coated conductor does not show crack formation in the insulating resin coating layer compared to an unstretched insulating coated conductor, and the minimum winding diameter at which no cracks occur is measured in the range from the self-diameter (1d) to n times the self-diameter (nd).

[0074] The following describes a method for producing the silica sol and insulating resin composition of the present invention, but the method for producing the silica sol and insulating resin composition of the present invention is not limited to those described below.

[0075] (Method for producing silica sol) A method for producing silica sol according to one embodiment involves the following steps (A) to (D): (A) Step: Prepare silica sol A in which silica particles are dispersed in an aqueous medium. (B) Step: A silane compound (a) is added to the silica sol A obtained in step (A) to obtain silica sol B containing silica particles having the hydrophilic group on their surface. (C) Step: The dispersion medium of silica sol B obtained in step (B) is replaced with a nitrogen-containing solvent to obtain silica sol C. (D) Step: A silane compound (b) is added to the silica sol C obtained in step (C) to obtain silica sol D containing silica particles having the hydrophilic group and the hydrophobic group on its surface. Includes.

[0076] (A) The silica sol A used in step (A) is preferably an acidic aqueous silica sol with a pH of 1.0 to 7.0, more preferably 2.0 to 5.0. The concentration of silica particles in silica sol A is preferably in the range of 0.1 to 50% by mass, or more preferably in the range of 10 to 40% by mass.

[0077] In step (B), the silane compound (a) undergoes a hydrolysis reaction and then reacts with the surface of the silica particles to form siloxane bonds (covalent bonds) on the surface of the silica particles, thereby obtaining silica sol B containing silica particles having hydrophilic groups on their surface. Specifically, the hydrophilic groups originate from the silane compound (a), where the alkoxy groups in the silane compound (a) are converted to -OH by hydrolysis, and further, at least one -OH group per molecule of the silane compound (a) reacts with the silanol groups (Si-OH) on the surface of the silica particles to form the siloxane bond -Si-O-Si-. In this process, groups other than the alkoxy groups in the silane compound (a) may be converted to hydroxyl groups. In step (B), for example, the reaction can be carried out at 50-100°C or 60-90°C for 0.1-10 hours. This reaction is preferably carried out at an acidic pH.

[0078] Water is required for the hydrolysis reaction of the above silane compound (a), and any aqueous solvent sol can be used. In particular, if the silane compound (a) contains an epoxy group and the hydrolysis of the silane compound (a) is intended to open the ring of the epoxy group to produce two hydroxyl groups, the hydrolysis reaction of the silane compound (a) should be carried out in an aqueous solvent to effectively open the ring of the epoxy group. Furthermore, the hydrolysis reaction can be carried out with or without a catalyst.

[0079] When hydrolysis is performed without a catalyst, the silica particle surface is on the acidic side. When a catalyst is used, examples of hydrolysis catalysts include metal chelate compounds, organic acids, inorganic acids, organic bases, and inorganic bases. Examples of metal chelate compounds as hydrolysis catalysts include triethoxy mono(acetylacetonate) titanium and triethoxy mono(acetylacetonate) zirconium. Examples of organic acids as hydrolysis catalysts include acetic acid and oxalic acid. Examples of inorganic acids as hydrolysis catalysts include hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, and phosphoric acid. Examples of organic bases as hydrolysis catalysts include pyridine, pyrrole, piperazine, and quaternary ammonium salts. Examples of inorganic bases as hydrolysis catalysts include ammonia, sodium hydroxide, and potassium hydroxide.

[0080] Step (C) is a step in which the dispersion medium of silica sol B obtained in step (B) is replaced with a nitrogen-containing solvent to obtain silica sol C. It is preferable to use an amide-type solvent as the nitrogen-containing solvent, for example, dimethylacetamide, dimethylformamide, N-methylpyrrolidone, or N-ethylpyrrolidone. In the solvent replacement with a nitrogen-containing solvent, the water content can be adjusted to a range of 0.1 to 4.0% by mass, 1.0 to 2.5% by mass, or 1.5 to 2.0% by mass in the total solvent.

[0081] In step (D), silane compound (b) is added to silica sol C obtained in step (C) to obtain silica sol D containing silica particles having hydrophilic and hydrophobic groups on their surface. Specifically, the hydrophobic groups originate from silane compound (b), and the alkoxy groups in silane compound (b) are hydrolyzed to -OH, and furthermore, at least one -OH per molecule of silane compound (b) reacts with the silanol group (Si-OH) on the surface of the silica particles to form a siloxane bond -Si-O-Si-. Step (D) can be carried out, for example, at 50-100°C or 60-90°C for 0.1-10 hours.

[0082] The hydrolysis of the above silane compound (b) requires water, but if an aqueous solvent sol is available, then those aqueous solvents can be used. Furthermore, the hydrolysis can be carried out with or without a catalyst.

[0083] When hydrolysis is performed without a catalyst, the silica particle surface is on the acidic side. When a catalyst is used, examples of hydrolysis catalysts include metal chelate compounds, organic acids, inorganic acids, organic bases, and inorganic bases. Examples of metal chelate compounds as hydrolysis catalysts include triethoxy mono(acetylacetonate) titanium and triethoxy mono(acetylacetonate) zirconium. Examples of organic acids as hydrolysis catalysts include acetic acid and oxalic acid. Examples of inorganic acids as hydrolysis catalysts include hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, and phosphoric acid. Examples of organic bases as hydrolysis catalysts include pyridine, pyrrole, piperazine, and quaternary ammonium salts. Examples of inorganic bases as hydrolysis catalysts include ammonia, sodium hydroxide, and potassium hydroxide.

[0084] (Method for manufacturing an insulating resin composition) The method for producing the insulating resin composition of the present invention further includes step (E) after steps (A) to (D) above: (E) Step: (E) Step, in which silica sol D, obtained in step (D) by dispersing silica particles in a nitrogen-containing solvent, is mixed with a nitrogen-containing polymer to obtain silica sol E. Includes.

[0085] In step (E), silica sol E is obtained by mixing and stirring the silica sol D obtained in step (D) with the polymer using a mixer or disperser. Additives can be added to silica sol E as desired. [Examples]

[0086] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. (Analysis method) The analytical methods used in the examples and comparative examples are shown below.

[0087] [Measurement of silica concentration (SiO2 concentration)] The silica sol was placed in a crucible, dried at 150°C, and the resulting gel was calcined at 1000°C under air for 30 minutes. The calcination residue was then weighed and calculated.

[0088] [Measurement of average primary particle diameter (particle diameter by nitrogen adsorption method)] Specific surface area value (S) of silica particles by nitrogen adsorption method in aqueous silica sol N2 In this study, water-soluble cations in a water-dispersed silica sol were removed using an H-type cation exchange resin (Dow Chemical, product name: Amberlite IR-120B), and the silica sol was dried at 290°C to prepare the sample for measurement. This sample was then measured using a nitrogen adsorption specific surface area analyzer, product name Monosorb (Quantachrome Instruments Japan LLC), with a mixed gas of 30% N2 (nitrogen) and 70% He (helium) as the carrier gas, using the BET single-point method. Specific surface area value (S) of silica particles by nitrogen adsorption method in organic solvent-dispersed silica sol N2 The specific surface area S was measured using the BET single-point method described above, with the measurement sample (silica particles (powder) heated at 150°C) obtained in the (measurement of carbon content) described later. N2 (m 2 ( / g) and density ρ (g / cm³) 3 From this, the average primary particle diameter (nm) = 6000 / ρ × S N2 The density of silica particles is calculated as follows: 3 ) is 2.2 (g / cm³) 3 ) was calculated as follows.

[0089] [Measurement of moisture content] The moisture content was determined by Karl Fischer titration using a Karl Fischer moisture meter (manufactured by Kyoto Electronics Manufacturing Co., Ltd., product name: MKA-610).

[0090] [pH measurement] The pH of the aqueous-dispersed silica sol was measured at 20°C using a pH meter (manufactured by Toa DKK Co., Ltd., product name: MM-43X). The pH of the organic solvent-dispersed silica sol was measured at 20°C using a solution prepared by mixing silica sol and pure water in a 1:1 mass ratio when the organic solvent used as the dispersion medium was methanol (MeOH), or by mixing silica sol, MeOH, and pure water in a 1:1:1 mass ratio when the organic solvent was a nitrogen-containing solvent, such as dimethylacetamide (DMAC).

[0091] [Measuring viscosity] The viscosity of the silica sol was measured at 20°C using an Ostwald viscometer. The viscosity of polyamic acid was measured at 25°C using an E-type viscometer.

[0092] [Measurement of average particle size using dynamic light scattering (DLS) method] The average particle diameter (average secondary particle diameter due to dynamic light scattering: also called Z-average particle diameter or DLS average particle diameter) measured by the DLS method was measured using a dynamic light scattering particle diameter analyzer (Malvern Panalytical, product name: Zetasizer Nano). 0.1 g of the target silica sol was placed in a glass cell with a path length of 10 mm, and the solvent, which is the main component of the dispersion medium of the silica sol, was added to obtain a silica sol with a silica particle concentration adjusted so that the count rate at attenuator 7 was 200-400 kcps. For example, MeOH was added to silica sols with methanol as the main component, and DMAC was added to silica sols with DMAC as the main component, so that the silica particle concentration was adjusted so that the count rate at attenuator 7 was 200-400 kcps. The prepared silica sol was placed in the cell, adjusted so that the liquid level was approximately 1 cm from the bottom of the cell, and the DLS average particle diameter of the silica sol was measured using attenuator 7.

[0093] [Solid content of polyamic acid] The polyamic acid was placed in an aluminum cup, then fired at 200°C, and the residual amount after firing was weighed and calculated.

[0094] [Measurement of Carbon Content] (1) Place 3 mL of organic solvent-dispersed silica sol in a 30 cc centrifuge tube, and add 20 mL of toluene. (2) After centrifuging with a centrifuge (centrifugal force 11000G × 30 minutes), remove the supernatant liquid. (3) Add 4 mL of acetone to redissolve the gel, then add 4 mL of toluene and 10 mL of hexane, perform centrifugation (centrifugal force 11000G × 30 minutes), and then remove the supernatant liquid. (4) Further repeat step (3) once more. (5) The obtained gel was vacuum-dried at 60°C, then the resulting powder was ground in a mortar, and dried at 150°C for 2 hours to obtain silica powder. For the powder obtained above, the carbon content (mass%) was measured using an elemental analyzer (manufactured by PerkinElmer, product name 2400II CHNS / O). (6) Using the nitrogen content from elemental analysis, the carbon content C corresponding to the solvent adsorbed on the silica particles (for example, DMAC: dimethylacetamide, etc.) s was calculated, and by subtracting it from the carbon content C of the powder obtained in (5) M , the carbon content (mass%) bonded to the silica particles was quantified as shown in Formula (I). Carbon content (mass%) derived from silane compound = [(C м − C S ) ···Formula (I) C м : Carbon content of the powder (mass%) C S : Carbon content corresponding to the solvent adsorbed on the silica particles (mass%)

[0095] [Hansen Solubility Parameter (HSP) Calculation] Using calculation software Winmstar (Cross-Ability Co., Ltd.), the HSP values of hydrosilanes (a) and (b), silane compound (c), and the silane compounds of Comparative Examples 1 to 4, as well as the HSP values of the matrix resin unit structure, were calculated. For the calculation of HSP, δD1, δP1 and δH1 of hydrosilane (a), as illustrated and explained in the above formulas (I) to (III), the silane compound (a) corresponding to the hydrophilic group was defined, and the HSP, δD1, δP1 and δH1 were calculated for the hydrosilane (a) obtained by substituting H (hydrogen atom) for the alkoxy group of the silane compound (a). For the calculation of HSP, δD4, δP4 and δH4 of hydrosilane (b), as illustrated and explained in the above formulas (IV) to (VI), the silane compound (b) corresponding to the hydrophobic group was defined, and the HSP, δD4, δP4 and δH4 were calculated for the hydrosilane (b) obtained by substituting H (hydrogen atom) for the alkoxy group of the silane compound (b). For the calculation of HSP, δD5, δP5 and δH5 of silane compound (c), as illustrated and explained in the above formulas (VII) to (XV), the HSP calculation was performed on the silane compound (c) having the organic groups contained in the hydrophilic group and the hydrophobic group in accordance with the above rules (1) to (3). In addition, for the silane compounds of Comparative Examples 1 to 4, HSP, δD5, δP5 and δH5 were calculated for the silane compounds having organic groups contained in hydrophilic groups and / or hydrophobic groups in accordance with the above rules (1) to (3). Furthermore, regarding HSP, δD2, δP2 and δH2, and δD3, δP3 and δH3 of the matrix resin unit structure, the bonding sites between the monomers, which are the repeating units of the corresponding nitrogen-containing polymer, were cleaved, and a structure was obtained in which H (hydrogen atom) was added to the cleaved sites (the above formulas (1) and (2)).

[0096] [Tensile Test of Two-Layer Silica-Filled Polyimide Film] Tensile test specimens prepared in Examples and Comparative Examples described later were subjected to a tensile test at a tensile speed of 10 mm / min and a distance between grips of 20 mm using a tabletop precision universal testing machine, model AGS-5kNX, manufactured by Shimadzu Corporation. The tensile test was performed 10 times, Ratio (%) of delamination of the polyimide two-layer film during the tensile test = (Number of times the polyimide two-layer film delaminated during the tensile test) / (Total 10 tensile test times) × 100 The adhesion between PI / PI layers was evaluated by calculating [a specific value]. Furthermore, the tensile tests were evaluated on a four-point scale from A to D as described below. The results obtained are shown in Table 1 below. <Evaluation Criteria for PI / PI Interlayer Adhesion by Tensile Test> A: Less than 10% of the polyimide two-layer film delamination occurs during tensile testing. B: The percentage of polyimide two-layer film delamination during tensile testing is between 10% and 30%. C: The percentage of polyimide two-layer film delamination during tensile testing is 30% or more but less than 60%. D: The rate of delamination between the two polyimide layers during tensile testing is 60% or higher.

[0097] (Example 1) (A) Step: As silica sol A, water-dispersed silica sol ST-O-33 (average primary particle size 12 nm, pH 3, silica concentration 33% by mass, manufactured by Nissan Chemical Corporation) was prepared. (B) Step: 1000 g of water-dispersed silica sol ST-O-33 (average primary particle size 12 nm, pH 3, silica concentration 33% by mass, manufactured by Nissan Chemical Corporation) was placed in a 2 L round-bottom flask, and 29.8 g of 3-glycidoxypropyltrimethoxysilane (silane compound (a); manufactured by Shin-Etsu Chemical Co., Ltd., trade name KBM-403) was added at 25°C while stirring the sol with a magnetic stirrer. After this, the liquid temperature was raised to 80°C and held under reflux in a condenser for 2 hours to obtain a water-dispersed silica sol (silica sol B) containing silica particles on the surface that have a hydrophilic group (-O)3Si(CH2)3OCH2CH(OH)CH2(OH) on its surface, which is formed by the ring-opening of the epoxy group of 3-glycidoxypropyltrimethoxysilane. (C) Step: The above water-dispersed silica sol was supplied with DMAC (dimethylacetamide) while the solvent was evaporated from it using a rotary evaporator at a reduced pressure of 170-110 Torr and a bath temperature of 105-125°C, thereby replacing the dispersion medium of the sol with DMAC, and a DMAC-dispersed silica sol (silica sol C; silica concentration 30.5% by mass, pH 4.5, viscosity (20°C) 4 mPa·s, water content 0.1% by mass, average secondary particle diameter 14 nm by DLS method, carbon content 2.5% by mass) was obtained.

[0098] (Example 2) Except for changing the raw material in step (A) of Example 1 to water-dispersible silica sol ST-OS (average primary particle size 9 nm, pH 2.8, silica concentration 20% by weight, manufactured by Nissan Chemical Corporation) and changing the amount of 3-glycidoxypropyltrimethoxysilane (silane compound (a)) added in step (B) of Example 1 to 24.3 g, the procedure was carried out in the same manner as in Example 1 to obtain DMAC-dispersed silica sol (silica sol C; silica concentration 31.0% by mass, pH 4.7, viscosity (20℃) 8 mPa·s, water content 0.1% by mass, average secondary particle size 30 nm by DLS method, carbon content 3.0% by mass).

[0099] (Example 3) (A) Step: As silica sol A, water-dispersed silica sol ST-O-33 (average primary particle size 12 nm, pH 3, silica concentration 33% by mass, manufactured by Nissan Chemical Corporation) was prepared. (B) Step: 1000 g of water-dispersed silica sol ST-O-33 (average primary particle size 12 nm, pH 3, silica concentration 33% by mass, manufactured by Nissan Chemical Corporation) was placed in a 2 L round-bottom flask, and 29.8 g of 3-glycidoxypropyltrimethoxysilane (silane compound (a); manufactured by Shin-Etsu Chemical Co., Ltd., trade name KBM-403) was added at 25°C while stirring the sol with a magnetic stirrer. After this, the liquid temperature was raised to 80°C and held under reflux in a condenser for 2 hours to obtain a water-dispersed silica sol (silica sol B) containing silica particles having (-O)3Si(CH2)3OCH2CH(OH)CH2(OH) on its surface as a hydrophilic group containing two hydroxyl groups formed by ring-opening of the epoxy group of 3-glycidoxypropyltrimethoxysilane. (C) Step: The above water-dispersed silica sol was supplied with DMAC (dimethylacetamide) while the solvent was evaporated off in a rotary evaporator at a reduced pressure of 170-110 Torr and a bath temperature of 105-125°C, thereby replacing the dispersion medium of the sol with DMAC, and a DMAC-dispersed silica sol (silica sol C; silica concentration 29.9% by mass, water content 2.0% by mass) treated with 3-glycidoxypropyltrimethoxysilane was obtained. (D) Step: Next, while stirring the above DMAC-dispersed silica sol with a magnetic stirrer, 25.0 g of phenyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name KBM-103) was added at 25°C as a hydroxyl group-free silane compound (b), and the liquid temperature was raised to 80°C and held for 2 hours. After that, the solvent was evaporated using a rotary evaporator at a reduced pressure of 150-110 Torr and a bath temperature of 105-125°C to obtain a DMAC-dispersed silica sol (silica sol D; silica concentration 30.7% by mass, pH 4.2, viscosity (20°C) 5 mPa·s, water content 0.1% by mass, average secondary particle size 13 nm by DLS method, carbon content 3.7% by mass).

[0100] (Example 4) In Example 3, the procedure was carried out in the same manner as in Example 3, except that the hydroxyl group-free silane compound (b) was replaced with 17.2 g of methyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name KBM-13) in step (D), to obtain a DMAC-dispersed silica sol (silica sol D; silica concentration 30.5% by mass, pH 4.2, viscosity (20℃) 5 mPa·s, moisture content 0.1% by mass, average secondary particle diameter 18 nm by DLS method, carbon content 2.7% by mass).

[0101] (Example 5) Except for changing the silane compound (a) in step (B) of Example 1 to 33.1 g of 3-trimethoxypropyl succinic anhydride (manufactured by Shin-Etsu Chemical Co., Ltd., trade name X-12-967C), the same procedure as in Example 1 was carried out to obtain a DMAC-dispersed silica sol (silica sol C; silica concentration 30.8% by mass, pH 4.4, viscosity (20℃) 8 mPa·s, moisture content 0.2% by mass, average secondary particle diameter 24 nm by DLS method, carbon content 2.5% by mass).

[0102] (Example 6) Except for changing the silane compound (a) in step (B) of Example 3 to 33.1 g of 3-trimethoxypropyl succinic anhydride (manufactured by Shin-Etsu Chemical Co., Ltd., trade name X-12-967C), the same procedure as in Example 3 was carried out to obtain a DMAC-dispersed silica sol (silica sol D; silica concentration 30.7% by mass, pH 4.2, viscosity (20℃) 5 mPa·s, moisture content 0.1% by mass, average secondary particle diameter 13 nm by DLS method, carbon content 3.4% by mass).

[0103] (Comparative Example 1) (A) Step: A methanol-dispersed silica sol MT-ST (average primary particle size 12 nm, silica concentration 30% by mass, manufactured by Nissan Chemical Corporation) was prepared. (B) Step: 1000 g of methanol-dispersed silica sol MT-ST (average primary particle size 12 nm, silica concentration 30% by mass, manufactured by Nissan Chemical Corporation) was placed in a 2 L round-bottom flask. While stirring the sol with a magnetic stirrer, 22.8 g of phenyltrimethoxysilane was added, and the liquid temperature was maintained at 60°C for 5 hours. Next, 46.6 g of hexamethyldisiloxane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name KF-96L) and 150 g of DMAC (dimethylacetamide) were added, and the liquid temperature was maintained at 60°C for 3 hours to hydrolyze the hexamethyldisiloxane and form trimethylsilyl groups on the surface of the silica particles. (C) Step: Subsequently, DMAC was supplied in a rotary evaporator while evaporating the solvent at a reduced pressure of 450-110 Torr and a bath temperature of 85-125°C, thereby replacing the dispersion medium of the sol with DMAC to obtain a DMAC-dispersed silica sol (silica concentration 30.6% by mass, pH 5.1, viscosity (20°C) 4 mPa·s, moisture content 0.1% by mass, average secondary particle diameter 13 nm by DLS method, carbon content 2.3% by mass).

[0104] (Comparative Example 2) In Comparative Example 1, the raw material in step (A) was changed to methanol-dispersed silica sol MA-ST-S (average primary particle size 9 nm, silica concentration 20% by weight, manufactured by Nissan Chemical Corporation), and in step (B) of Comparative Example 1, the amount of phenyltrimethoxysilane added was changed to 20.4 g and the amount of hexamethyldisiloxane added was changed to 62.2 g. The procedure was carried out in the same manner as in Comparative Example 1 to obtain DMAC-dispersed silica sol (silica concentration 30.7% by mass, pH 4.6, viscosity (20℃) 3 mPa·s, moisture content 0.1% by mass, average secondary particle size 10 nm by DLS method, carbon content 3.2% by mass).

[0105] (Comparative Example 3) (A) Step: A water-dispersible silica sol ST-O-33 (average primary particle size 12 nm, pH 3, silica concentration 33% by mass, manufactured by Nissan Chemical Corporation) was prepared. (B) Step: 1000 g of the aqueous silica sol prepared in step (A) was placed in a 2 L round-bottom flask. While stirring the sol with a magnetic stirrer, 200 g of DMAC (dimethylacetamide) was added, followed by 0.8 g of N,N-diisopropylethylamine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and then the mixture was held at 25°C for 30 minutes. (C) Step: The sol obtained in step (B) was supplied with DMAC while the solvent was evaporated using a rotary evaporator at a reduced pressure of 300-120 Torr and a bath temperature of 108°C, thereby replacing the dispersion medium of the sol with DMAC to obtain a DMAC-dispersed silica sol (silica concentration 31.9% by mass, water content 4.0% by mass). (D) Step: Next, 25.1 g of phenyltrimethoxysilane was added to the DMAC-dispersed silica sol obtained in step (C) while stirring with a magnetic stirrer. After this, the liquid temperature was maintained at 90°C for 1 hour. Then, 1.8 g of N,N-diisopropylethylamine was added and the liquid temperature was maintained at 90°C for 1 hour. (E) Step: The sol obtained in step (D) was subjected to solvent replacement using the same method as in step (C) to obtain a DMAC-dispersed silica sol (silica concentration 30.4% by mass, pH 5.2, viscosity (20℃) 4 mPa·s, water content 0.1% by mass, average secondary particle size 15 nm by DLS method, carbon content 2.0% by mass).

[0106] (Comparative Example 4) In step (B) of Example 3, the same operation as in Example 3 was carried out except that the silane compound was changed to 26.0 g of hexyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name KBM-3063), to obtain a DMAC-dispersed silica sol (silica concentration 30.5 mass%, pH 5.2, viscosity (20°C) 5 mPa·s, water content 0.1 mass%, average secondary particle diameter by DLS method 16 nm, carbon content 3.5 mass%).

[0107] (Synthesis Example 1) Preparation of polyamic acid 496 g of 4,4'-diaminodiphenyl ether (DDE), 534 g of pyromellitic dianhydride (PMDA), and NMP (N-methylpyrrolidone) and DMAC (dimethylacetamide) as solvents were used, and polymerization was carried out at a temperature of 50°C for 13 hours under stirring, to obtain a polyamic acid corresponding to formula (8) (solid content 17 mass%, viscosity at 25°C measured by E-type viscometer 13640 mPa·s). In the polymerization of the polyamic acid, the above DDE and PMDA were polymerized at an equimolar ratio of 1:1. The weight average molecular weight of the obtained polyamic acid was 63000. In formula (8), n is the number of repeating units.

Chemical Formula

[0108] (Reference example 1) A sample for tensile testing was obtained using the same procedure as in Synthesis Example 1, except that DMAC-dispersed silica sol was not added.

[0109] For the DMAC-dispersed silica sols obtained in Examples 1-6 and Comparative Examples 1-4, tensile test samples were prepared using the procedure of Synthesis Example 1. Along with Reference Example 1, the adhesion between the first silica-containing polyimide film and the second silica-containing polyimide film was evaluated according to the above-described [Tensile Test of Two-Layer Silica-Based Polyimide Films].

[0110] For the DMAC-dispersed silica sols obtained in Examples 1-6 and Comparative Examples 1-4, the HSPs of hydrosilane (a), silane compound (c), and matrix resin unit structures (structures of formulas (1) and (2)), as well as their dispersion term, polarity term, and hydrogen bonding term, were calculated according to the Hansen solubility parameter (HSP) calculation described above.

[0111] [HSP] Hydrosilane (a), silane compound (c), and the HSP of the silane compounds of Comparative Examples 1-4, as well as the interaction distance D z Examples 3, 4, and 6 are shown in Table 1. [Table 1] The following formulas (9) to (16) represent the structures of the hydrosilanes listed in Table 1 above. [ka] [ka]

[0112] [HSP of matrix resin unit structure] Table 2 shows the HSP, dispersion term, polarity term, and hydrogen bonding term of the matrix resin unit structure (structures of formulas (1) and (2) above). [Table 2]

[0113] Table 3 shows the HSPs of hydrosilane (a) (Examples 1, 2, 5), silane compound (c) (Examples 3, 4, 6), silane compound (Comparative Examples 1-4), and the HSPs and interaction distance D of the matrix resin unit structure (structure of formula (1) above). x , D z1 , D y , D z2 The results of the adhesion evaluation are shown. [Table 3]

[0114] From the results in Table 3, the interaction distance D of the DMAC-dispersed silica sols obtained in Examples 1-6 x , D z1 , D y , D z2 The interaction distance D is 14.1 to 16.3 for Comparative Examples 1 to 4. x , D z1 , D y , D z2 It is clear that the silica particles are smaller and have a high affinity for polyimide resins that have repeating units corresponding to the matrix resin unit structure (structures of formulas (1) and (2) above). Furthermore, the peeling rate of the DMAC-dispersed silica sols obtained in Examples 1 to 6 was 0%, which is higher than the peeling rates of 45% to 82% in Comparative Examples 1 to 4, indicating that the interlayer adhesion of the two-layer film consisting of the first and second silica-containing polyimide films can be improved. Note that, as shown in Reference Example 1, the peeling rate was 0% for the two-layer film of polyimide film without added silica particles, but this may pose problems in terms of insulation resistance, etc., because silica particles are not added. [Industrial applicability]

[0115] This invention provides a silica sol in which silica particles, which have excellent affinity with nitrogen-containing polymers such as polyimide and polyamide, are dispersed in a nitrogen-containing solvent. This invention also provides an insulating resin composition in which these silica sols are combined with nitrogen-containing polymers. Furthermore, this invention provides an insulating coated wire in which, when a coating layer consisting of multiple layers of insulating resin is formed using the insulating resin composition, there is no delamination between layers, and a long insulating life is possible.

Claims

1. A silica sol comprising a nitrogen-containing solvent and silica particles dispersed in the nitrogen-containing solvent, The silica particles have an average primary particle diameter of 5 to 100 nm. At least a portion of the silica particles have hydrophilic groups on their surface that originate from the hydrolysis of silane compound (a) and contain hydroxyl groups bonded to carbon atoms. The polar term (δP) that constitutes the Hansen solubility parameter (HSP) in hydrosilane (a), obtained by substituting the alkoxy group of the silane compound (a) with a hydrogen atom. 1 ) 2.0 to 30.0 MPa 0.5 , hydrogen bond term (δH 1 ) 3.0 to 30.0 MPa 0.5 That is silica sol.

2. The interaction distance D between the hydrosilane (a) and the matrix resin unit structure represented by the following formula (1) x 17.0 MPa 0.5 The following applies: The interaction distance D x The silica sol according to claim 1, which is represented by the following formula (A). 【number】 [Math 1] (In the above formula (A), δD 1 , δP 1 , and δH 1 each represent the dispersion term, polar term, and hydrogen bonding term that constitute the Hansen Solubility Parameter (HSP) in hydrosilane (a), δD 2 δP 2 , and δH 2 (Each of these terms represents the dispersion term, polarity term, and hydrogen bonding term that constitute the Hansen solubility parameter (HSP) in the matrix resin unit structure represented by formula (1).)

3. The interaction distance D between the hydrosilane (a) and the matrix resin unit structure represented by the following formula (2) y 17.0 MPa 0.5 The following applies: The interaction distance D y The silica sol according to claim 1, which is represented by the following formula (B). 【number】 [Math 2] (In the above formula (B), δD 1 δP 1 , and δH 1 These terms represent the dispersion term, polar term, and hydrogen bonding term that constitute the Hansen solubility parameter (HSP) in hydrosilane (a), respectively. δD 3 δP 3 , and δH 3 (Each of these terms represents the dispersion term, polarity term, and hydrogen bonding term that constitute the Hansen solubility parameter (HSP) in the matrix resin unit structure represented by formula (2).)

4. An insulating resin composition prepared under the following preparation conditions is applied to a glass plate and heated at 290°C for 1 hour in an atmospheric environment to form a first silica-containing polyimide film having a thickness of 15 to 20 μm. An insulating resin composition prepared under the following preparation conditions is applied to a first silica-containing polyimide film, and heated at 290°C for 1 hour in an atmospheric environment to form a second silica-containing polyimide film having a thickness of 15 to 20 μm. The silica sol according to claim 1, wherein when 10 of the two-layer films, each consisting of a first and a second silica-containing polyimide film, are produced by peeling them off the glass plate, and each of the two-layer films is subjected to a tensile test, the percentage of delamination between the first silica-containing polyimide film and the second silica-containing polyimide film, calculated as (number of times the two-layer film delaminates) / (10 times) × 100, is less than 30%. [Preparation conditions for insulating resin compositions] A polyamic acid consisting of 4,4'-diaminodiphenyl ether (DDE) and pyromellitic anhydride (PMDA) (DDE and PMDA are polymerized in an equimolar 1:1 ratio, with a solid content of 17% by mass and a weight-average molecular weight of 63,000) is used as the resin, and the silica sol is mixed with it in a mass ratio of resin / SiO 2 An insulating resin composition is prepared so that the ratio is 80 / 20.

5. At least a portion of the silica particles further have hydrophobic groups on their surface that originate from the hydrolysis of silane compound (b) and do not contain hydroxyl groups bonded to carbon atoms. The interaction distance D between the hydrosilane (a) and hydrosilane (b) obtained by substituting the alkoxy group of the silane compound (b) with a hydrogen atom. z 5.0 MPa 0.5 That concludes the explanation. The interaction distance D z The silica sol according to claim 1, which is represented by the following formula (C). [Math 3] (In the above formula (C), δD 1 δP 1 , and δH 1 These terms represent the dispersion term, polar term, and hydrogen bonding term that constitute the Hansen solubility parameter (HSP) in hydrosilane (a), respectively. δD 4 δP 4 , and δH 4 (These terms represent the dispersion, polarity, and hydrogen bonding components that constitute the Hansen solubility parameter (HSP) in hydrosilane (b), respectively.)

6. The silica sol according to claim 1, wherein the hydrophilic group is represented by the following formula (3). 【Transformation 3】 (In the above formula (3), R 1 , R 2 and R 3 Each of these independently represents -O- or an organic group, R 1 , R 2 and R 3 (At least one of these groups is an organic group containing a hydroxyl group.)

7. The organic group having a hydroxyl group in formula (3) is -CH(OH)-CH 2 The silica sol according to claim 6, having (OH).

8. At least a portion of the silica particles further have hydrophobic groups on their surface that originate from the hydrolysis of silane compound (b) and do not contain hydroxyl groups bonded to carbon atoms. The silica sol according to claim 6, wherein the hydrophobic group is represented by the following formula (4). 【Chemistry 4】 (In the above formula (4), R 4 , R 5 and R 6 Each of these independently represents an organic group that does not have an -O- or hydroxyl group, and R 4 , R 5 and R 6 (At least one of these groups is the aforementioned organic group.)

9. The silica sol according to claim 8, wherein the organic group of formula (4) is an alkyl group, a halogenated alkyl group, an alkenyl group, an aryl group, or a group having a (meth)acryloyl group, a mercapto group, a ureido group, or a cyano group.

10. The interaction distance D between the silane compound (c) having all the organic groups constituting the hydrophilic group and all the organic groups constituting the hydrophobic group and the matrix resin unit structure represented by the following formula (1) z1 17.0 MPa 0.5 The following applies: The interaction distance D z1 The silica sol according to claim 8, which is represented by the following formula (D). 【number】 [Math 4] (In the above formula (D), δD 5 δP 5 , and δH 5 These terms represent the dispersion term, polarity term, and hydrogen bonding term that constitute the Hansen solubility parameter (HSP) in silane compound (c), respectively. δD 2 δP 2 , and δH 2 (Each of these terms represents the dispersion term, polarity term, and hydrogen bonding term that constitute the Hansen solubility parameter (HSP) in the matrix resin unit structure represented by formula (1).)

11. The interaction distance D between the silane compound (c) having all the organic groups constituting the hydrophilic group and all the organic groups constituting the hydrophobic group and the matrix resin unit structure represented by the following formula (2) z2 17.0 MPa 0.5 The following applies: The interaction distance D z2 The silica sol according to claim 8, which is represented by the following formula (E). 【number】 [Math 5] (In the above formula (E), δD 5 δP 5 , and δH 5 These terms represent the dispersion term, polarity term, and hydrogen bonding term that constitute the Hansen solubility parameter (HSP) in silane compound (c), respectively. δD 3 δP 3 , and δH 3 (Each of these terms represents the dispersion term, polarity term, and hydrogen bonding term that constitute the Hansen solubility parameter (HSP) in the matrix resin unit structure represented by formula (2).)

12. The silica sol according to claim 1, wherein the nitrogen-containing solvent is an amide-based solvent.

13. The silica sol according to claim 12, wherein the nitrogen-containing solvent is dimethylacetamide, dimethylformamide, N-methylpyrrolidone, or N-ethylpyrrolidone.

14. An insulating resin composition comprising a silica sol according to any one of claims 1 to 13 and a nitrogen-containing polymer.

15. The insulating resin composition according to claim 14, wherein the content of the nitrogen-containing polymer is 1 to 100 parts by mass per 1 part by mass of silica particles contained in the silica sol.

16. The insulating resin composition according to claim 14, wherein the nitrogen-containing polymer is polyimide, polyamide, polyamic acid, polyamideimide, polyetherimide, or polyesterimide.

17. The insulating resin composition according to claim 16, wherein the nitrogen-containing polymer is a polymer comprising repeating units represented by the following formula (8). 【Transformation 7】

18. Wires and, A cured layer of the insulating resin composition according to claim 14 for covering the aforementioned conductor, comprising a cured layer consisting of two or more layers, An insulating coated conductor having [a certain characteristic].

Citation Information

Patent Citations

  • Inverter surge resistant enameled wire

    JP2000331539A

  • Process of producing inorganic oxide organosol

    JP2005200294A

  • Method for producing silica-based fine particle-dispersed sol, silica-based fine particle-dispersed sol, coating composition containing silica-based fine particle-dispersed sol, curable coating film, and base with curable coating film

    JP2011026183A

  • Epoxy resin-forming liquid preparation containing inorganic particle

    WO2009008509A1

  • Aluminum-containing silica sol dispersed in nitrogen-containing solvent, and resin composition

    WO2022097694A1